Relation of heart-type fatty acid-binding protein with the degree and extent of atherosclerosis in patients with non-ST elevation acute coronary syndrome - Gönül Zeren; Hatice Betül Erer; Tuncay Kırış; Osman Şahin; Hüseyin Aksu; Diyar Köprülü; Tolga Sinan Güvenç; Güney Erdoğan; Nurten Sayar; Zeki Yüksel Günaydın; Mehmet Eren (KARE Publishing, 2013)
Objectives: The relationship between markers of myocardial ischemia and severity of coronary artery disease (CAD) has been investigated in several studies. In this study, we examined the relationship between severity of CAD and heart-type fatty acid-binding protein (H-FABP), a new marker of ischemia in patients with non-ST-segment elevation acute coronary syndrome (ACS). Study design: This prospective study comprised 49 patients who were referred to the emergency room with a diagnosis of non-ST elevation myocardial infarction. Troponins, creatine kinase-MB, lactate dehydrogenase, and aspartate aminotransferase levels were measured quantitatively, while blood H-FABP levels were measured qualitatively in the 4th- 8th hour from the onset of symptoms. All patients underwent coronary angiography within 72 hours after admission. Clinical and coronary angiographic characteristics of patients with positive and negative values of H-FABP were compared. Gensini and SYNTAX scores were used to determine the severity of CAD. Results: There were no statistically significant differences in mean age, gender distribution, risk factors for CAD, ischemic changes on ECG, or Gensini and SYNTAX scores between the H-FABP-negative and -positive groups (p>0.05). The duration of chest pain in the H-FABP-positive group was significantly longer than in the negative group (p<0.001). Troponin, CK-MB, and AST levels as well as thrombolysis in myocardial infarction (TIMI) risk scores were found to be significantly higher in the H-FABP-positive group (p<0.05). Conclusion: H-FABP is a useful marker for the diagnosis and risk evaluation of patients with non-ST elevation ACS. However, it is insufficient in evaluating the severity of CAD.